Rethinking Recovery: Incorporating Holistic Nursing Perspectives in Poststroke Care. Issue 1 (January 2017) - Peterson-Burch, Frances; Reuter-Rice, Karin; Barr, Taura L.
Abstract : Stroke is a life-changing experience. Current treatments focus on treating the condition, rather than the whole person. The goal of this report was to communicate the benefits of a holistic approach to the treatment and recovery of stroke. Our intent was to begin a conversation to transform our approach to stroke care to focus on the whole person, body, mind, and spirit. Wellness approaches are fiscally responsible ways of providing holistic care for patients and their family members to help them achieve optimal individualized recovery. Very few multidimensional programs for wellness exist for patients with stroke and brain injury. Given the changes in health care and the Call to Action set forth in the Institute of Medicine's 2010 report, it would behoove us to consider holistic approaches to stroke care and research programs. Nurses are uniquely positioned to implement multidisciplinary, innovative holistic approaches to address solutions for issues in stroke care. Wellness is a critically important area of stroke care and an opportunity for research. As advocates for patients, and nurses with personal experiences, we hope this commentary stimulates conversation around developing and testing multidimensional holistic programs of wellness for stroke prevention, treatment, and recovery.